Optimalisasi Strategi Pengelolaan Kelas dalam Meningkatkan Kedisiplinan Siswa - Rahmania, Cici Aulia; Yudistira, Chantika Putri; Syahira, Khadijah Khansa; Aulia, Sabrina Shafa; Mustikaati, Wina (Universitas Pahlawan Tuanku Tambusai, 2025)
This article discusses the importance of optimizing classroom management strategies to improve student discipline. Through an effective approach, it is hoped that it can create a conducive learning environment and encourage students to be more disciplined in following the learning process. To answer this goal, the author chooses a library research method by utilizing relevant literature. The results of the literature review show that to improve student discipline, teachers need several methods of carrying out classroom management. The results show that the application of clear and consistent rules can increase student motivation and discipline. In addition, the importance of good communication between teachers and students was also identified as a key factor in creating a positive learning atmosphere. Thus, optimizing classroom management strategies is an important step in achieving better educational goals.